An aspartic protease 47 causes quantitative recessive resistance to rice black‐streaked dwarf virus disease and southern rice black‐streaked dwarf virus disease. Issue 6 (30th January 2022) - Wang, Zhaoyun; Zhou, Lian; Lan, Ying; Li, Xuejuan; Wang, Jian; Dong, Jingfang; Guo, Wei; Jing, Dedao; Liu, Qing; Zhang, Shaohong; Liu, Zhiyang; Shi, Wenjuan; et al.
Summary: Rice black‐streaked dwarf virus disease (RBSDVD) and southern rice black‐streaked dwarf virus disease (SRBSDVD) are the most destructive viral diseases in rice. Progress is limited in breeding due to lack of resistance resource and inadequate knowledge on the underlying functional gene. Using genome‐wide association study (GWAS), linkage disequilibrium (LD) decay analyses, RNA‐sequencing, and genome editing, we identified a highly RBSDVD‐resistant variety and its first functional gene. A highly RBSDVD‐resistant variety W44 was identified through extensive evaluation of a diverse international rice panel. Seventeen quantitative trait loci (QTLs) were identified among which qRBSDV6‐1 had the largest phenotypic effect. It was finely mapped to a 0.8–1.2 Mb region on chromosome 6, with 62 annotated genes. Analysis of the candidate genes underlying qRBSDV6‐1 showed high expression of aspartic proteinase 47 ( OsAP47 ) in a susceptible variety, W122, and a low resistance variety, W44. OsAP47 overexpressing lines exhibited significantly reduced resistance, while the knockout mutants exhibited significantly reduced SRBSDVD and RBSDVD severity. Furthermore, the resistant allele Hap1 of OsAP47 is almost exclusive to Indica, but rare in Japonica . Results suggest that OsAP47 knockout by editing is effective for improving RBSDVD and SRBSDVD resistance. This study provides genetic information for breeding resistant cultivars.